Estudo socioestilístico da alternância pronominal entre nós e a gente no português falado no noroeste paulista - Nardelli, Alex Junior dos Santos (2021)
Based on the foundations of Variationist Sociolinguistics (LABOV, 1972; WEINREICH;en LABOV; HERZOG, 1968), on the studies on stylistic/discursive variation (HORA, 2014; GÖRSKI et. al., 2014; FREITAG, 2009) and style (LABOV, 1972; ECKERT, 1989; 2012; 2005), this work presents the results of the analysis of the first-person plural (1PP) pronominal alternation (AP) in Portuguese spoken in São Paulo, considering the two types of sample that make up the Iboruna database of the ALIP Project - Linguistic Sample of São Paulo State: Census Sample (AC), recorded with the prior consent of the informants and, therefore, with a higher degree of speech monitoring, and Interaction Sample (AI), secretly recorded, with the subsequent consent of the informants and, therefore, with a lower degree of speech monitoring. The analysis of the variable phenomenon made based on the evaluation of the individual performances of AC and AI informants seeks to ascertain how much the degree of speech monitoring that emerges from the stylistic differences of the collected speech samples and the different social profiles of informants influence the application of the variable rule. We analyzed the AP between “nós” and “a gente”, starting from the pairing of the same social profiles of AI and AC informants, in order to verify how much, in fact, speech monitoring interferes with the performance/linguistic style of individual informants. The unproven hypothesis assumes that in less monitored speech styles, such as AI, certain social profiles would show more use of the innovative variant to “a gente” when compared to the same social profiles of AC, that would further preserve the use of the conservative variant to “nós”. Based on the concept that the results of the analysis of a variable phenomenon for a speech community generalize and minimize the individual performance of informants, the present study points out sociolinguistic results different from those found for the analysis of the speech community, since, in the analysis of the different individual styles of the social profiles of AI, the use of the variant “nós” predominate over that of “a gente”, with marked difference in relation to the same social profiles of AC. This general result innovates due to the consideration of discursive/stylistic variables in the analysis of the AP of 1PP and allows to conclude that (i) the innovative variant “a gente” are completely embedded in the linguistic and social system of the variety spoken in the interior of São Paulo, taking into account that results for formal variables do not differ from those achieved for the speech community study (RUBIO, 2012); (ii) the innovative variant compared to the conservative variant cannot be considered a social indexer; (iii) it is no longer possible to maintain that there is a difference in status between the nodes and people variants and (iv) for a sociostylistic approach to the phenomenon, discursive variables are more relevant than structural variables.